Respuesta de tres genotipos de tomate al cultivo in vitro y aislamiento de protoplastos (2011)
ABSTRACT: The goal of this study was to evaluate the best plant material source for protoplast isolation, cell suspensions or leaf mesophyll cells in three tomato genotypes with different levels of resistance to Phytophthora infestans: Solanum habrochaites (503) resistant, S. lycopersicum (507) susceptible, and the hybrid partially resistant (508). after the in vitro establishment from certi ed seeds of the 503 and 507 genotypes, and cuttings of the 508 genotype, the leaves from the developed and multiplied plantlets were used for callus induction. four growth regulator combinations per genotype and two light conditions were evaluated, with the highest percentages of callus formation under dark conditions. the combinations of regulators with greatest effect on growth and callus friability were Bap (1 ppm) + iaa (4 ppm) for the 503 genotype and Bap (4 ppm) + iaa (1 ppm) for the 507 and 508 genotypes. these combinations of regulators were used for the establishment of cell suspensions and plotting of the cell growth curve. protoplast isolation from cell suspensions was conducted in the exponential phase, evaluating different enzymatic mixtures and incubation times; however, no response was obtained for any genotype. from mesophyll, 1.2 x 105 protoplasts/ml with high viability were obtained for the 503 genotype (0.6% cellulose and 0.1% pectinase, 8 h incubation); 1.9 x 105 protoplasts/ml for the 507 genotype (4% cellulose and 0.4% pectinase, 8 h incubation); and 1.1 x 105 protoplasts/ml for the 508 genotype (2% cellulose and 0.2% pectinase, 7 h incubation). Key words: callus, mesophyll,suspension cells, Solanum lycopersicum, Solanum habrochaites.